Manhaj Muqtarah Li Ta’lîm Al-Lughah Al-‘Arabiyah Min Khilâl Al-Mufradât Al-Indûnisiyah Dzâtu Ashlin Qurânî - Husni Arif; Mulyadi (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2021)
لقد وجد الباحث عددًا غير قليل من المفردات الإندونيسية ذات أصل عربي في القرآن، فأطلق مصطلح لهذه المفردات بالمفردات الإندونيسية ذات أصل قرآني. من هذه الظاهرة يرى الباحث إمكانية تعليم اللغة العربية من خلال هذه المفردات. بناءً على المنهج الوصفي التحليلي يحاول الباحث تحليل المفردات الإندونيسية ذات أصل قرآني في بحث فتح رحمن، ثم استخدام هذه المفردات لبناء منهج مقترح لتعليم اللغة العربية من خلالها. توصل الباحث إلى نتائج: رصد المفردات الإندونيسية ذات أصل قرآني التي جمعها فتح رحمن في بحثه من قبل واختيار بعض المفردات، ومن هذه المفردات يمكن بناء منهج تعليم اللغة العربية من خلالها، وذلك بوضع هذه المفردات في الحوارات، ثم يأتي دور المدرس لبيان هذه المفردات وينمي مهارات اللغة العربية الأربع من خلال تدريسه. Researchers have found several Indonesian vocabularies originating from Arabic in the quran.And then researchers looked at the possibility of teaching Arabic through this vocabulary. The method in this study is a qualitative approach. Based on the descriptive analysis method, the researcher tries to analyze Indonesian vocabulary from the origin of the quran. in FathurRohman's research, then uses this vocabulary to build a proposed curriculum for teaching Arabic. The results of the study are as follows: Researchers have selected some Indonesian vocabulary from the origin of the quran. compiled by FathurRahman in his previous research, and from this vocabulary it is possible to develop Arabic teaching methodologies through this, by placing this vocabulary in dialogue, then the teacher's role for explain this vocabulary and develop the Four Arabic language skills through teaching.